Soil temperature, volumetric water content, electrical conductivity, air temperature and atmospheric pressure measured every 10 minutes in a grass- and a herb-dominated area at a summer dike, Butjadingen, Germany (Nov 2022–Nov 2023) - Jan-Michael Schönebeck; Dorothea Bunzel; Maike Paul; Torsten Schlurmann (PANGAEA, 2025)
To understand the role of plant species and functional diversity on the physical soil parameters of a sea dike, especially under prolonged drought conditions, continuous measurements of soil temperature, volumetric water content (soil moisture), soil electrical conductivity (EC), air temperature and atmospheric pressure were carried out from 22 November, 2022, to 22 November, 2023. The measurements were taken using six soil sensors from METER Group extquotesingles TEROS 12 series, which were installed at three distinct soil depths (4 cm, 14 cm, 24 cm) and on two differently vegetated dike areas: one area with a grass-dominated plant community (referred to as extquotesingleMix-Grass extquotesingle) and one area with a herb-dominated plant community (referred to as extquotesingleMix-Herb extquotesingle). The sensors were mounted on the southern (inland) side of a summer dike, which is located at the south-eastern North Sea coast of Germany (Butjadingen, Wesermarsch; extquotesingleMix-Grass extquotesingle: 53.61211876 ° N, 8.330925695° E, extquotesingleMix-Herb extquotesingle: 53. 61210826° N, 8.330989015° E), about 1 m below the dike crest. The dike height is approximately 3.6 m above mean high water (MHW). The measurement data was logged at 10-minute intervals using a ZL6 logger from the METER Group.